Injuries outside of horseracing: is it time to focus on injury prevention of jockeys outside of races? - O`Connor, S.; Warrington, G.; O`Brien, S.; McDermott, E.; McGoldrick, A.; Pugh, J.; Cullen, S. J. (The Physician and Sportsmedicine, 2021)
Objectives: Falls and injuries are frequent in professional horseracing. However, professional jockeys spend a large part of their week in horse-related activities outside of racing such as schooling, exercise riding, and yard-related activities. The injury risk related to these activities remains largely unknown internationally. This study aimed to identify the injury prevalence and injury profile of flat and jump jockeys during non-racing activities.